Copper alloy sheet material and method for manufacturing the same, as well as heat dissipation components, electrical components, and electronic components using copper alloy sheet material
Patent Information
- Application Number
- JP2026043115
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-07-14
- Filing Date
- 2026-03-17
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167532000010 
Figure 2026167532000011 
Figure 2026167532000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a copper alloy sheet material suitable for highly conductive materials and heat dissipation component materials, and to a method for manufacturing the same. [Background technology]
[0002] In recent years, electrification and automation have progressed in fields such as automobiles, and the highly conductive materials and heat dissipation materials used in these fields require properties such as high conductivity and high strength.
[0003] Patent Document 1 describes a copper alloy sheet containing 0 to 1.0 mass% of Ag, 0 to 0.08 mass% of Ti, 0 to 2.0 mass% of Ni, 0 to 3.5 mass% of Zn, and a total of 0 to 0.5 mass% of one or more elements selected from the group consisting of Cr, Fe, In, P, Si, Sn, and Zr, with the remainder being Cu and unavoidable impurities, and by controlling the degree of accumulation of crystal orientations in the rolling direction on the sheet surface, a copper alloy sheet with excellent heat dissipation, conductivity, repeated bending processability, and shape retention is provided.
[0004] Patent Document 2 discloses a copper alloy plate that combines high conductivity and heat resistance, containing 0.0005% to 0.1% by mass of Ni, 0.0005% to 0.1% by mass of Sn, 100 ppm or less of C, 800 ppm or less of O, 10 ppm or less of H, and 50 ppm or less of Ag, with the remainder being Cu and impurities. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2014-080679 [Patent Document 2] Japanese Patent Publication No. 2023-005017 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] Patent documents 1 and 2 also illustrate highly conductive materials with conductivity of 95% IACS or higher. However, like pure copper-based materials such as oxygen-free copper and tough pitch copper, these materials have few compound particles and high ductility, making them sensitive to changes in processing conditions such as clearance when punching out conductive components by press working. In other words, changes in clearance can easily result in differences in the quality of the product cross-section. Quality refers to, for example, the shear surface / fracture surface ratio, which is the ratio of the size of the shear surface to the fracture surface in the product cross-section. The present invention aims to provide a copper alloy sheet material that has high conductivity and excellent properties of minimal change in the shear surface / fracture surface ratio even when the clearance / thickness ratio changes (this property will be referred to as "press punchability" in this specification). [Means for solving the problem]
[0007] This invention was made under the circumstances described above. In order to solve the above-mentioned problems, the inventors conducted diligent research and found that even in pure copper-based materials, by generating a predetermined number or more compound particles of a predetermined size range, it is possible to provide a copper alloy sheet material with excellent press-punching properties while maintaining high conductivity.
[0008] In other words, the first invention that solves the above-mentioned problems is a compound comprising 0.0005% to 0.1% by mass of Ni, 0% to 0.1% by mass of Sn, 0% to 0.02% by mass of Fe, 0% to 0.02% by mass of P, 0% to 0.02% by mass of Zn, 0% to 0.1% by mass of Mg, and 10 ppm to 200 ppm by mass of O, with the remainder being Cu and impurities, wherein the total content of Ni, Sn, P, Fe, Zn, and Mg is 0.001% to 0.11% by mass, and the number density of compound particles with a major axis of 0.03 μm to 4.00 μm on an observation surface parallel to the plate surface is 10,000 particles / mm². 2 That concludes the description of the copper alloy sheet material.
[0009] The second invention is a copper alloy plate material as described in the first invention, wherein the conductivity is 95% IACS or more and 102% IACS or less. The third invention is a copper alloy plate material according to the first or second invention, wherein the average major diameter of the compound particles is 0.035 to 3.00 μm. The fourth invention is a copper alloy sheet material according to any of the first to third inventions, wherein when the copper alloy sheet material is press-punched in a direction parallel to the rolling direction with clearance / thickness ratios of 0.08 and 0.19, the change in the shear surface ratio (shear surface length / fracture surface length) of the end face is 3.0 or less. The fifth invention is a copper alloy plate material according to any of the first to fourth inventions, containing 0% by mass or more and 0.05% by mass of Zn.
[0010] The sixth invention is a heat dissipation component using a copper alloy plate material as described in any of the first to fifth inventions. The seventh invention is an electrical component using a copper alloy plate material as described in any of the first to fifth inventions. The eighth invention is an electronic component in which a copper alloy plate material described in any of the first to fifth inventions is joined to an insulating substrate.
[0011] The ninth invention relates to the production of copper alloy sheet material in a process including a melting step, a casting step, a heat treatment step, a hot rolling step, a cold rolling step, an intermediate annealing step, and a finish cold rolling step, In the melting process described above, pure copper raw material is heated and melted, and the oxygen content in the resulting molten metal is controlled to be between 20 ppm by mass and 200 ppm by mass. Subsequently, additive elements are added to the molten metal so that its chemical composition is as follows: Ni: 0.0005% by mass or more and 0.1% by mass or less, Sn: 0% by mass or more and 0.1% by mass or less, Fe: 0% by mass or more and 0.02% by mass or less, P: 0% by mass or more and 0.02% by mass or less, Zn: 0% by mass or more and 0.1% by mass or less, Mg: 0% by mass or more and 0.05% by mass or less, O: 10 ppm by mass or more and 200 ppm by mass or less, remainder: Cu and impurities, and the total content of Ni, Sn, Fe, P, Zn and Mg is 0.001% by mass or more and 0.11% by mass or less. In the casting step, the molten metal obtained in the melting step is poured into a mold through the molten metal flow path and the tundish, and cast to obtain an ingot. The molten metal flow path has a portion where the molten metal flowing through the flow path is exposed to the atmosphere, 3 to 50 kg of the molten metal passes through the portion in 1 to 15 seconds, and when the molten metal flow path is viewed from above, at the portion exposed to the atmosphere, the width of the molten metal is 30 to 90 mm, and the area of the molten metal surface is 5,000 to 450,000 mm 2 , and In the heat treatment step, the ingot obtained in the casting step is heat-treated at a temperature of 700°C to 900°C for 30 minutes to 10 hours, In the hot rolling step, the ingot softened in the heat treatment step is hot-rolled at 900°C or lower. This is a method for producing a copper alloy sheet material.
Effects of the Invention
[0012] The pure copper-based copper alloy sheet material according to the present invention is excellent in press punchability while maintaining high electrical conductivity by forming a predetermined amount of a compound of a predetermined size.
Brief Description of the Drawings
[0013] [Figure 1] This is a schematic cross-sectional view showing the positional relationship between the cutting blade corresponding to the punch, the material (test material), and the cutting blade corresponding to the die in the evaluation of press punchability. [Figure 2] In the evaluation of press punchability, this is a diagram of the sheared material (test material) with the cut surface (left side) and the view of the cut surface from the direction parallel to the rolling direction and opposite in orientation (right side) (corresponding to the cut surface when the cut end is cut perpendicular to the rolling direction).
Modes for Carrying Out the Invention
[0014] Hereinafter, the copper alloy sheet material according to the present invention will be described in the order of [1] Composition, [2] Method for producing copper alloy sheet material, [3] Properties and evaluation methods, and [4] Heat dissipation components, current-carrying components, and electronic components using the copper alloy sheet material.
[0015] In the present specification, "plate material" refers to a sheet-shaped metal material. A thin sheet-shaped metal material may sometimes be referred to as "foil", and such "foil" is also included in the "plate material" as referred to herein. A long sheet-shaped metal material wound into a coil is also included in the "plate material". Further, in the present specification, the thickness of the sheet-shaped metal material is referred to as "plate thickness". The "plate surface" means a surface perpendicular to the plate thickness direction of the plate material. The plate surface may also be referred to as "rolled surface".
[0016] In the present specification, the notation "n1 to n2" indicating a numerical range means "not less than n1 and not more than n2". Here, n1 and n2 are numerical values satisfying n1 < n2.
[0017] The rolling reduction (%) in a certain rolling process is determined by the following formula (1). Rolling reduction (%) = 100 × (h0 - h1) / h0 … (1) h0: Plate thickness (mm) before being subjected to the first rolling pass of the rolling process h1: Plate thickness (mm) when the final rolling pass of the rolling process is completed
[0018] [1] Composition The composition of the copper alloy plate material according to the present invention includes Ni of 0.0005 mass% or more and 0.1 mass% or less, Sn of 0 mass% or more and 0.1 mass% or less, Fe of 0 mass% or more and 0.02 mass% or less, P of 0 mass% or more and 0.02 mass% or less, Zn of 0 mass% or more and 0.1 mass% or less, Mg of 0 mass% or more and 0.05 mass% or less, and O of 10 mass ppm or more and 200 mass ppm or less, with the balance being Cu and impurities, wherein the total content of the aforementioned Ni, Sn, P, Fe, Zn and Mg is 0.001 mass% or more and 0.11 mass% or less. The term "0 mass%" means, for each element (excluding Ni and O) described below, that the content is less than the lower limit of quantitation (not detected) when measured by a quantitative apparatus.
[0019] The following describes the effects and content of Ni and other components such as Sn contained in the copper alloy sheet material according to the present invention, in the order of (1) Ni, (2) Sn, (3) Fe, (4) P, (5) Zn, (6) Mg, (7) O, and (8) the total content of Ni, Sn, Fe, P, Zn, and Mg.
[0020] (1) Ni (nickel) Ni reacts with oxygen (O), etc., to form compound particles such as Ni oxide, which are then finely dispersed in the matrix, contributing to improved press-punching properties. It is difficult to fully achieve these effects when the Ni content is less than 0.0005% by mass. Therefore, the Ni content must be 0.0005% by mass or more, preferably 0.001% by mass or more, more preferably 0.002% by mass or more, and most preferably 0.003% by mass or more. On the other hand, if the Ni content is excessive, the conductivity tends to decrease. Therefore, the Ni content must be 0.1% by mass or less, preferably 0.08% by mass or less, more preferably 0.05% by mass or less, and most preferably 0.02% by mass or less. Furthermore, within the specified range of this invention, a high Ni content tends to result in larger compound particle sizes.
[0021] (2) Sn (Tin) Sn contributes to improved press-punching performance by forming compound particles composed of compounds with O, etc., and finely dispersing them in the matrix. To achieve this effect, the Sn content is preferably 0.0005% by mass or more, more preferably 0.001% by mass or more, even more preferably 0.002% by mass or more, and most preferably 0.0025% by mass or more. On the other hand, if the Sn content is excessive, the conductivity tends to decrease. Therefore, the Sn content needs to be 0.1% by mass or less, preferably 0.08% by mass or less, even more preferably 0.05% by mass or less, and most preferably 0.02% by mass or less. Note that Sn does not need to be contained in the copper alloy sheet material (it may be below the lower limit of quantification (undetectable) when measured with a quantitative device). Also, if the Sn content is high within the range specified in this invention, the size of the compound particles tends to increase.
[0022] (3) Fe (iron) Fe is expected to contribute to improved press-punching performance by forming compound particles consisting of compounds with P, O, etc., and finely dispersing them in the matrix. However, excessive Fe content can lead to a decrease in conductivity, so it is necessary to limit it to a range of 0.02 mass% or less, preferably 0.01 mass% or less, more preferably 0.008 mass% or less, and most preferably 0.006 mass% or less. Fe does not necessarily have to be contained in the copper alloy sheet material (it may be below the lower limit of quantification (undetectable) when measured with a quantitative device). If Fe is included, the Fe content is preferably 0.001 mass% or more, and more preferably 0.002 mass% or more. Also, within the range specified in this invention, if the Fe content is high, the size of the compound particles tends to increase.
[0023] (4) P (Lin) While phosphorus (P) generally contributes as a deoxidizing agent for copper alloys, in this invention, it contributes to improved press-punching properties by forming compound particles such as Fe-P compounds and Mg-P compounds and finely dispersing them in a Cu matrix. To achieve this effect, the P content is preferably 0.0005% by mass or more. However, excessive P content can lead to a decrease in conductivity, so it is necessary to limit it to a range of 0.02% by mass or less, preferably 0.01% by mass or less, more preferably 0.008% by mass or less, and most preferably 0.007% by mass or less. Note that P does not necessarily have to be contained in the copper alloy sheet material (it may be below the lower limit of quantification (undetectable) when measured with a quantitative device). Also, if the P content is high within the range specified in this invention, the size of the compound particles tends to increase.
[0024] (5) Zn (zinc) Zn is expected to contribute to improved press-punching performance by forming compound particles consisting of compounds with O, etc., and finely dispersing them in the matrix. However, excessive Zn content can lead to a decrease in conductivity, so it is necessary to limit it to a range of 0.1 mass% or less, preferably 0.05 mass% or less, more preferably 0.04 mass% or less, particularly preferably 0.03 mass% or less, and most preferably 0.02 mass% or less. Note that Zn does not have to be contained in the copper alloy sheet material (it may be below the lower limit of quantification (undetectable) when measured with a quantitative device). If Zn is included, the Zn content is preferably 0.0005 mass% or more, and more preferably 0.001 mass% or more.
[0025] (6) Mg (Magnesium) Mg is expected to contribute to improved press-punching performance by forming compound particles consisting of compounds with P, O, etc., and finely dispersing them in the Cu matrix. However, excessive Mg content can cause hot cracking, so it is necessary to limit it to a range of 0.05 mass% or less, preferably 0.04 mass% or less, more preferably 0.03 mass% or less, and most preferably 0.02 mass% or less. Note that Mg does not have to be contained in the copper alloy sheet material (it may be below the lower limit of quantification (undetectable) when measured with a quantitative device). If Mg is contained, the Mg content is preferably 0.0001 mass% or more.
[0026] (7) O (oxygen) O is introduced during the melting process from the manufacturing raw materials and the atmosphere. If the O content is high, blowholes and blistering may occur in the copper alloy sheet material. Generally, the amount of O is reduced by controlling the deoxidizing agent and atmosphere. In the present invention, a predetermined amount of O is incorporated into the manufacturing raw materials and casting process to form compound particles consisting of oxides with Sn, Fe, Mg, etc., thereby improving press punchability. Therefore, the O content in the copper alloy sheet material of the present invention manufactured through the casting process, etc., must be 10 ppm by mass or more, preferably 20 ppm by mass or more, and more preferably 50 ppm by mass or more. On the other hand, if the O content is excessive, blowholes and blistering are likely to occur, so the O content must be 200 ppm by mass or less, preferably 180 ppm by mass or less, more preferably 165 ppm by mass or less, and most preferably 100 ppm by mass or less.
[0027] (8) Total content of Ni, Sn, Fe, P, Zn, and Mg The total content of Ni, Sn, P, Fe, Zn, and Mg shall be between 0.001% by mass and 0.11% by mass. If the total content of these elements is too low, a predetermined amount of compound particles consisting of intermetallic compounds and metal oxides cannot be secured, making it impossible to disperse them in the Cu matrix and improve the press-punching properties of the copper alloy sheet material. Conversely, if the total content of these elements is too high, the conductivity tends to decrease. The total content may be controlled between 0.005% by mass and 0.08% by mass, and from the viewpoint of conductivity, it is preferable to control it between 0.005% by mass and 0.033% by mass.
[0028] (9) Remainder Cu and unavoidable impurities The chemical composition of the copper alloy sheet material of the present invention can be specified as consisting of the elements mentioned above, with the remainder being Cu and unavoidable impurities. In other words, in the present invention, elements other than Ni, Sn, Fe, P, Zn, Mg, O, and Cu are considered impurities. As the total amount of these impurity elements increases, the conductivity of the copper alloy sheet material decreases. From the viewpoint of achieving high conductivity, in the copper alloy sheet material of the present invention, the impurity content (the total content of impurity elements) is preferably 20 ppm by mass or less, and more preferably less than 10 ppm by mass.
[0029] In the copper alloy plate material according to the present invention, impurities are defined as elements that can be quantified by inductively coupled plasma emission spectroscopy (ICP-OES, e.g., Agilent 5900) or an oxygen, nitrogen, and hydrogen analyzer (e.g., LECO ONH-836).
[0030] [2] Method for manufacturing copper alloy sheet As an example of a method for manufacturing copper alloy sheets according to the present invention, a method for manufacturing copper alloy sheets comprising the steps of (1) melting and casting, (2) heat treatment, (3) hot rolling, (4) cold rolling, (5) recrystallization annealing, (6) finish rolling, and (7) low-temperature annealing will be described for each step.
[0031] (1) Melting and casting This process involves mixing alloy raw materials in predetermined amounts to achieve the chemical composition of the copper alloy sheet material according to the present invention, heating and melting the mixture, and casting an ingot. In this invention, first, pure copper raw materials are heated and melted to control the oxygen content in the molten metal within a predetermined range, and then predetermined amounts of additive elements are mixed in to cast an ingot of a predetermined composition from the resulting molten metal. The pure copper raw materials preferably have a purity of 99.9% by mass or higher, and examples of commercially available products include oxygen-free copper and tough pitch copper. It is preferable to use these scrap materials in order to suppress raw material costs. Normally, when manufacturing pure copper products, pure copper materials such as oxygen-free copper are dissolved in a reducing atmosphere. However, in this invention, it is desirable to dissolve them in air in order to form a predetermined amount of compound particles. For example, the pure copper raw material is dissolved using a high-frequency melting furnace, and the oxygen content is controlled to be between 20 ppm by mass and 200 ppm by mass. Alternatively, the pure copper raw material may be dissolved in a non-oxidizing atmosphere such as a nitrogen atmosphere, and oxygen may be blown into the molten metal to control the oxygen content within the above range. Furthermore, if oxygen is incorporated into the molten metal from the atmosphere and the oxygen content exceeds 200 ppm by mass, it is preferable to add a reducing agent such as charcoal to the molten metal to control the oxygen content within the above range. Note that when the oxygen content is controlled to be 40 ppm by mass or more, preferably 65 ppm by mass or more, the size of the formed compound particles tends to increase.
[0032] After controlling the O content to between 20 ppm by mass and 200 ppm by mass, predetermined amounts of each additive element, such as Ni, are added. If the additive elements are added when the O content exceeds 200 ppm by mass, phenomena such as oxides formed by the oxidation of the additive elements during dissolution will occur and separate from the molten metal, making it difficult to achieve the number density of compound particles in the copper alloy sheet material of the present invention. Furthermore, if the O content is 20 ppm by mass or less, the oxygen concentration is too low, making it difficult to secure the number density of compound particles specified in the present invention in subsequent processes. In this invention, the O content in the molten metal refers to the amount of dissolved oxygen, and the method for measuring this will be explained in the examples.
[0033] The molten metal (molten metal), which has been melted in a high-frequency induction melting furnace and subjected to the above-mentioned oxygen content control and additive element blending, flows through a molten metal channel and is poured into the mold via a tundish. In this invention, the molten metal channel provided between the melting furnace and the tundish flows at a predetermined pace, and the molten metal channel is equipped with a section that is open to the atmosphere, so that the molten metal is exposed to the atmosphere to a predetermined extent. The pace at which the molten metal flows is such that 3 to 50 kg of molten metal passes through the section of the molten metal channel exposed to the atmosphere in 1 to 15 seconds. Furthermore, when the molten metal channel is viewed from above, the width of the molten metal (length in the direction perpendicular to the direction of flow of the molten metal on the molten metal surface) is 30 to 90 mm, and the surface area of the molten metal is 5,000 to 450,000 mm² at the section exposed to the atmosphere. 2 This is the process. Then, using the molten metal that has passed through the molten metal channel and flowed into the tundish, casting is performed in a mold to produce an ingot. By exposing the molten metal to the atmosphere under the above conditions in the molten metal channel, a predetermined amount of compound particles are formed. These compound particles are thought to be mainly metal oxides, and since their melting points are generally high, they are difficult to melt during heating in subsequent processes, and it is thought that most of them remain until the final product (copper alloy sheet material). In this invention, the entire amount of molten metal is flowed through the molten metal channel at once, the length of the molten metal flowing through the molten metal channel is longer than the length of the portion of the molten metal exposed to the atmosphere (the dimension of that portion in the direction in which the molten metal flows), and the surface area of the molten metal is the product of the width of the molten metal and the length of the portion exposed to the atmosphere. Furthermore, the molten metal in areas of the molten metal channel other than the portion exposed to the atmosphere (for example, inside the tundish) is covered with a flux such as carbon to minimize contact with the atmosphere.
[0034] (2) Heat treatment The heat treatment process involves applying heat treatment to the ingot obtained in the melting and casting process described above. This process, which preferably involves heat treatment of the ingot at a temperature of 700°C to 900°C for 30 minutes to 10 hours, has the macroscopic effect of reducing elemental segregation that occurred during casting. Heat treatment at temperatures exceeding 900°C may promote the redissolution of compound particles formed in the copper alloy; therefore, it is preferable to perform the heat treatment at temperatures below 900°C.
[0035] (3) Hot rolling In the hot rolling process, the ingot is rolled after being softened at a high temperature during the heat treatment described above. This is done to soften the copper alloy material through recrystallization during rolling and between rolling passes, and to break down the cast structure in the ingot. In this rolling process, rolling at temperatures exceeding 900°C may lead to increased remelting of compound particles formed in the copper alloy, or cracking in areas with lower melting points, such as segregated alloy components. Therefore, it is preferable to roll at temperatures below 900°C. Furthermore, in order to ensure that complete recrystallization, where the entire cast structure becomes a recrystallized structure, occurs during the hot rolling process, it is preferable to roll at a temperature range of 650 to 900°C (based on the ingot thickness) with a rolling ratio of 70% or more.
[0036] (4) Cold rolling (rough rolling) Cold rolling is a rough rolling process that reduces the thickness of the ingot after hot rolling. Therefore, it is desirable that the rolling ratio be 50% or more. This process is important for the subsequent recrystallization annealing (intermediate annealing) process, as it introduces strain into the ingot after hot rolling. The introduced strain becomes the driving force for recrystallization. If the rolling ratio is 50% or more, it is thought that the size of the recrystallized grains will be suitably uniform in the subsequent recrystallization annealing process. However, if the rolling ratio exceeds 95%, cracks may occur on the edge of the copper alloy sheet, and there is a risk of fracture, so it is preferable to keep the rolling ratio below 95%.
[0037] (5) Annealing (intermediate annealing) Annealing is a process in which a sheet material that has been cold-rolled is heat-treated to recrystallize and soften the structure that has been work-hardened by cold rolling. The heat treatment is preferably held at a temperature of 250 to 750°C for several seconds to several hours. If the temperature is above 250°C, recrystallization will proceed sufficiently. On the other hand, if the temperature exceeds 750°C, the grain size will become coarse, and it may not be possible to obtain a copper alloy sheet material with the desired strength. Furthermore, cold rolling and annealing may be repeated to achieve the desired plate thickness. In this case, it is preferable that the rolling ratio of the cold rolling (intermediate rolling) performed after the rough rolling but before the finish cold rolling be 10 to 80%.
[0038] (6) Finish cold rolling Finish cold rolling is a process performed to obtain a copper alloy sheet with the desired thickness from a sheet material that has undergone intermediate annealing, and to improve the strength level of the copper alloy sheet material. The rolling ratio is adjusted within the range of 0% (no finish rolling) to 95% depending on the desired strength level. If the finishing rolling ratio exceeds 95%, work hardening reaches its limit, the strength will not increase, the sheet material will have no elongation, and the bendability may deteriorate. The final thickness of the copper alloy sheet material is determined to be optimal depending on the application, but it is preferably around 0.02 to 6.0 mm, and more preferably between 0.04 and 5.0 mm.
[0039] (7) Low-temperature annealing Low-temperature annealing is a process performed as needed to improve bendability by reducing residual stress in the finished-rolled copper alloy sheet material, and to improve stress relaxation resistance by reducing voids and dislocations on the slip surfaces of the copper alloy sheet material. Low-temperature annealing is preferably performed by heat-treating the copper alloy sheet material at a temperature of 750°C or lower, and more preferably at a heating temperature of 150 to 470°C (preferably lower than the annealing temperature in the recrystallization annealing process described above). Furthermore, the holding time at this heating temperature is preferably 5 seconds or more in a continuous annealing furnace to suppress variations in the metal structure depending on the location during recrystallization annealing, and preferably within 10 hours in a batch annealing furnace for cost reasons.
[0040] [3] Characteristics and evaluation methods To evaluate the properties of the copper alloy sheet material according to the present invention, various evaluations were performed in the examples described later. The evaluation methods will be explained in the following order: (1) measurement of tensile strength, (2) measurement of electrical conductivity, (3) measurement of the number density of compound particles, and (4) evaluation of press punchability.
[0041] (1) Measurement of tensile strength Tensile strength was measured by taking a test specimen (JIS Z2201 No. 5 test specimen) for tensile testing in the LD (direction parallel to the rolling direction) from the copper alloy sheet material and performing a tensile test in accordance with JIS Z2241. To ensure sufficient strength as a component, the tensile strength is 230 N / mm². 2 The above is preferable. In the case of the copper alloy sheet material of the present invention, the tensile strength is more preferably 245 N / mm². 2 That concludes the explanation. The tensile strength is 360 N / mm². 2 The following may be used for management.
[0042] (2) Measurement of conductivity The conductivity was measured according to the conductivity measurement method specified in JIS H0505. The copper alloy plate material of the present invention has excellent conductivity, and more preferably has 94-102% IACS, more preferably 95-101.7% IACS, and even more preferably 96-101.5% IACS.
[0043] (3) Measurement of the number density of compound particles and the average major diameter of compound particles The number density of compound particles is determined by electrolytically polishing the plate surface of the copper alloy sheet material to dissolve only the Cu matrix, thereby exposing the compound particles, then rinsing off the electrolytic solution with running water and drying to obtain an observation surface, observing this observation surface with an FE-SEM (Field Emission Scanning Electron Microscope), counting the total number of compound particles with a major axis of 0.03 μm or more and 4.00 μm or less observed on the SEM image (secondary electron image), and calculating the value by dividing the total number by the area corresponding to the observation range of the above SEM image. In addition, the observation was performed on randomly set fields of view, and the observation magnification was set to 5000 times. Compound particles that partially protrude from the observation field of view were excluded from counting. Note that energy-dispersive X-ray spectroscopy (EDX) mounted on the SEM was used, and particles in which two or more elements were detected were counted as compound particles. From the perspective of achieving excellent press punchability, for the copper alloy sheet material, the number density of compound particles with a major axis of 0.03 μm or more and 4.00 μm or less is 10,000 particles / mm 2 or more. From a similar perspective, the number density of compound particles is preferably 11,000 particles / mm 2 or more. In the present invention, the number density may be controlled to 250,000 particles / mm 2 or less, or may be controlled to 150,000 particles / mm 2 or less. The compound particles only need to have their major axis satisfy the above range, and the minor axis is not particularly limited.
[0044] The measurement of the major axis of the compound particles and the counting of the total number of particles were performed using ImageJ (National Institutes of Health (NIH), Version 1.52a) in the following manner. First, the above SEM image was loaded into the software, and after sequentially selecting Analyze and Set Scale, the number of pixels of the scale bar length of the captured FE-SEM image was measured on the "Set Scale" screen and entered into Distance in pixels. Next, the scale bar length (μm) was entered into Known distance, the Pixel aspect ratio was set to 1.0, and the Unit of length was set to μm, so that the size of the compound particles could be recognized in the software. Then, on the "Resize Image Canvas" screen, the Width was set to 1280 pixels, the Height to 950 pixels, and the Position to Top-Center, and the image of the FE-SEM image portion excluding the scale bar was displayed. Subsequently, in the "Threshold" screen, which is displayed by sequentially selecting Image, Adjust, and Threshold, the brightness was inverted so that the pixel with the lowest brightness among all pixels had a brightness of 255 and the pixel with the highest brightness had a brightness of 0. The threshold was set to a value that brought the ratio of pixels below that value to all pixels closest to 0.03%, and the areas containing compound particles were binarized and identified. Then, in the "Analyze Particles" screen of the same software, the area of one independent compound particle region was 0.001 μm². 2 To exclude particles smaller than a certain size, the Size was set to "0.001-Infinity". Furthermore, the Circularity was set to 0.00-1.00, and the "Fit Ellipse" option was checked in the "Set Measurements" screen. Particle analysis was then performed, and the number of compound particles with a major axis (displayed under the "Major" item name) between 0.03 μm and 4.00 μm in that field of view was determined.
[0045] Furthermore, the average major diameter of the compound particles, which is obtained by adding up the major diameters of each counted compound particle (with a major diameter of 0.03 μm or more and 4.00 μm or less) and dividing by the total number of counted compound particles, is, for example, 0.035 to 3.00 μm. From the viewpoint of press punching properties, it is preferable that it be 0.13 μm or more. The average major diameter of the compound particles is 0.13 μm or more, and the number density of compound particles is 25,000 particles / mm³. 2 The above conditions result in particularly excellent press-punching properties. The average major diameter of the compound particles may be controlled to 2.40 μm or less, or to 1.80 μm or less. When the average major diameter of the compound particles is large, the number density of compound particles tends to decrease accordingly.
[0046] (4) Evaluation of press punching performance For press punching performance, a mechanical shear (Aizawa Seisakusho, AST-1313) was used to obtain a straight cut edge when viewed from the thickness direction of the test material (the test material was cut from a copper alloy sheet. The size was 10 mm in width in the rolling direction (LD) and 100 to 500 mm in length in the direction perpendicular to the rolling direction (TD)). As shown in Figure 1, the distance (clearance) between the punch side and the die side was adjusted so that the longitudinal direction of the cutting blade (upper movable blade) equivalent to the punch and the cutting blade (lower fixed blade) equivalent to the die were parallel to the rolling direction (LD) of the test material, and shearing (cutting) was performed with clearance / thickness ratios of 0.08 and 0.19. The cut surface of the material remaining on the table side, corresponding to the die, after being separated by shearing was observed using a laser microscope (Keyence Corporation, VKX-3000). Figure 2 is a schematic diagram of the cut surface. In Figure 2, LD represents the rolling direction, and PD represents the direction of travel of the cutting blade, which corresponds to the punch. The cut surface between A and D includes the shear surface between A and B, and the fracture surface between B and D. While the burr near the upper end A or the burr near the lower end D of the cut surface are generally not included in the shear or fracture surface, here, for convenience, the burr portion is included in the fracture surface only, in order to evaluate the proportion of the shear surface based on the cut surface morphology viewed almost from the front. The shear surface ratio was calculated using the following formula. The shear surface ratio is calculated as follows: (length of line segment AB) / (length of line segment BD). Line segments A-D were drawn from the center of the cut surface of the test material (5 mm from the edge in the width direction), and the above calculation was performed. The change in shear surface ratio was defined as the absolute difference in the shear surface ratio values for each clearance / plate thickness ratio. The copper alloy sheet material of the present invention exhibits excellent press punching properties, and the change in shear surface ratio is preferably 3.0 or less. According to the present invention, it is also possible to provide a copper alloy sheet material with a change of 2.5 or less, and even a change of 1.8 or less, and furthermore, a change of 1.0 or less. The change is usually 0.1 or more.
[0047] [4] Heat dissipation components, electrical components, and electronic components using copper alloy sheet material As described above, the copper alloy sheet material of the present invention has high conductivity and excellent press-formability, making it suitable for electrical components such as connectors and heat dissipation components for electronic devices. Furthermore, the copper alloy sheet material of the present invention may be bonded to an insulating substrate to form an electronic component. [Examples]
[0048] The copper alloy sheet material and its manufacturing method according to the present invention will be described in detail below with reference to the examples. However, the present invention is not limited to these examples.
[0049] [Example 1] Tough pitch copper (purity: 99.9% by mass or higher) was used as the pure copper raw material. It was melted in an air atmosphere using a high-frequency induction melting furnace, and then charcoal was added to reduce the oxygen in the molten pure copper raw material (hereinafter simply referred to as "molten metal"), adjusting the oxygen content to 44 ppm by mass. The oxygen content in the molten metal was measured using a zirconia oxygen sensor (manufactured by Nissab). This sensor can measure the amount of dissolved oxygen in the molten metal. Next, each additive element shown in Table 1 was added to the molten metal. Tables 1-3 show the chemical composition of the copper alloy sheets obtained in each example and comparative example. The oxygen content in the molten metal is shown in Tables 4-6 below. Regarding Comparative Example 5, the production of the copper alloy sheet (intermediate rolling) was interrupted due to numerous casting defects, as described later. The results of the compositional analysis of this sheet are shown in Table 3.
[0050] After adding additive elements to the molten metal, the copper alloy molten metal is stirred in a melting furnace for about 30 minutes. Then, in a molten metal channel located between the melting furnace and the tundish, which is open to the atmosphere (atmospheric exposure area), 27 kg of molten metal flows through the channel (amount of molten metal exposed to the atmosphere: 27 kg). When the molten metal in the atmospherically open section of the channel is viewed from above, the width of the molten metal exposed to the atmosphere (atmospheric exposure molten metal width) is 60 mm, and the area (atmospheric exposure molten metal area) is 252,500 mm². 2 The time it took for the molten metal to pass through the portion of the molten metal channel exposed to the atmosphere (the time it took for the molten metal to pass through the portion exposed to the atmosphere) was set to 8 seconds, and the molten metal that had passed through the molten metal channel and flowed into the tundish was poured into the mold for casting. At this time, in areas other than those exposed to the atmosphere, such as when inside the tundish, the surface of the molten metal was coated with carbon powder to minimize contact with the atmosphere as much as possible.
[0051] A 210mm thick ingot obtained by casting was subjected to homogenization heat treatment at 840°C for 4.5 hours, then hot-rolled to 11.8mm, and finally machined on both sides.
[0052] Next, the sheet was rolled from 10.9 mm to 2.0 mm thick by cold rolling (rough rolling). Then, the first intermediate annealing was performed at 410°C for 3 hours, and then it was rolled to a thickness of 0.94 mm by cold rolling.
[0053] Next, a second intermediate annealing was performed at 720°C for 26 seconds, followed by finish rolling to achieve a rolling reduction rate of 15%, resulting in a copper alloy sheet with a thickness of 0.80 mm. The above manufacturing conditions are summarized in Table 4 below.
[0054] Next, samples (test materials) were taken from the copper alloy sheet material obtained in Example 1, and their composition, tensile strength, electrical conductivity, compound number density, and press punchability were evaluated as follows. (1) Composition Analysis of the composition of the sample taken from the aforementioned copper alloy sheet material revealed, as shown in Table 1, that the Ni content was 0.0065 mass%, the Sn content was 0.0025 mass%, the Fe content was 0.0037 mass%, the P content was 0.003 mass%, the Zn content was 0.0013 mass%, the O content was 72 mass ppm, and the total content of Ni, Sn, Fe, P, Zn, and Mg was 0.017 mass%, with 5 mass ppm of S detected as an impurity. No other elements were detected. Since no elements were added or extracted during the manufacturing (rolling, etc.) of the copper alloy sheet material from the ingot, it is assumed that the ingot also had a similar composition.
[0055] The oxygen content in the sample was quantified using an oxygen, nitrogen, and hydrogen analyzer (LECO ONH-836). The oxygen content in the molten metal was measured using a zirconia oxygen sensor as described above. Other elements were quantified using a spark discharge emission spectrometer (Thermo Fisher Scientific ARL 4460 OES).
[0056] (2) Measurement of tensile strength The tensile strength was determined by taking a test specimen (JIS Z2201 No. 5 specimen) for tensile testing in the LD (direction parallel to the rolling direction) from a copper alloy sheet and performing a tensile test in accordance with JIS Z2241. As a result, the tensile strength of the LD was 270 N / mm².2 That was the case.
[0057] (3) Measurement of conductivity The conductivity was measured according to the conductivity measurement method of JIS H0505. As a result, the conductivity of the copper alloy plate material was 101.0% IACS.
[0058] (4) Number density and average major diameter of compound particles The number density of compound particles was determined by electrolytically polishing the surface of a copper alloy plate under the following electrolytic polishing conditions to dissolve only the Cu substrate and expose the compound particles. After washing off the electrolyte with running water and drying the observation surface, it was observed using a field emission scanning electron microscope (FE-SEM), and the total number of compound particles with a major axis of 0.03 μm to 4.0 μm observed on the SEM image (secondary electron image) using the method described above was counted. Observations were conducted using randomly selected fields of view, with a magnification of 5000x. Compound particles that partially extended beyond the observation field were excluded from the count. The total number of compound particles was measured over the observation area (mm²). 2 The value obtained by dividing by ) is the compound number density (particles / mm³). 2 The number density of the compound was calculated as follows: 57,739 particles / mm³. 2 Furthermore, in the EDX analysis, particles in which two or more elements were detected were classified as compound particles. The average major axis of the compound particles was calculated by adding up the major axes of each counted compound particle and dividing by the total number of counted compound particles, which was found to be 0.097 μm. (Electrolytic polishing conditions) • Electrolyte: Distilled water, phosphoric acid, ethanol, and 2-propanol were mixed in a volume ratio of 10:5:5:1. • Liquid temperature: 20℃ Voltage: 15V ·Electrolysis time: 18 seconds
[0059] (5) Press punching properties For press punching performance, a mechanical shear (Aizawa Seisakusho, AST-1313) was used to obtain a straight cut surface when viewed from the thickness direction of the test material (cut from copper alloy sheet material, with a width of 10 mm in the rolling direction (LD) and a length of 100-500 mm in the length direction (TD)). The cutting blade (upper movable blade) equivalent to a punch and the cutting blade (lower fixed blade) equivalent to a die were aligned parallel to the rolling direction (LD) of the test material, and shearing (cutting) was performed with clearance / thickness ratios of 0.08 and 0.19. When shearing was performed with a clearance of 0.064 mm, the clearance / plate thickness ratio was 0.08, resulting in a shear surface ratio of 3.0. When shearing was performed with a clearance of 0.15 mm, the clearance / plate thickness ratio was 0.19, resulting in a shear surface ratio of 1.3. The change in the shear surface ratio was 1.7.
[0060] [Example 2] Except for changing the chemical composition of the copper alloy as shown in Table 1 and performing low-temperature annealing at 560°C for 20 seconds after the final cold rolling, copper alloy sheets with the composition shown in Table 1 were manufactured under the same manufacturing conditions as Example 1 shown in Table 4. The same measurements as in Example 1 were performed on the copper alloy plate material according to Example 2. The measurement results are shown in Table 7 below.
[0061] [Example 3] The chemical composition of the copper alloy was changed as shown in Table 1, the oxygen content in the molten pure copper raw material was set to 73 ppm by mass, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was set to 299,000 mm². 2 Except for setting the width of the molten metal surface in the area exposed to the atmosphere to 80 mm and ensuring that 23 kg of molten metal passed through the aforementioned area in 7 seconds in the molten metal flow path provided between the melting furnace and the tundish, a copper alloy plate material with the composition shown in Table 1 was manufactured using the same manufacturing method as in Example 1 shown in Table 4. The same measurements as in Example 1 were performed on the copper alloy plate material according to Example 3. The measurement results are shown in Table 7 below.
[0062] [Example 4] Except for changing the chemical composition of the copper alloy as shown in Table 1, setting the rolling ratio for rough rolling (cold rolling) to 71%, the rolling ratio for intermediate rolling (cold rolling) to 34%, performing a second intermediate annealing at 410°C for 3 hours, and then setting the rolling ratio for finish cold rolling to 11%, a copper alloy sheet material with the composition shown in Table 1 was manufactured using the same manufacturing method as in Example 1 shown in Table 4. The sheet thickness after finish cold rolling was 2.00 mm. The copper alloy sheet material according to Example 4 was subjected to the same measurements as in Example 1. The clearance / sheet thickness ratio for press punching was set in the same manner as in Example 1. The measurement results are shown in Table 7 below.
[0063] [Example 5] The chemical composition of the copper alloy was changed as shown in Table 1, the oxygen content in the molten pure copper raw material was set to 71 ppm by mass, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was set to 187,000 mm². 2 A copper alloy sheet material with the composition shown in Table 1 was produced using the same manufacturing method as in Example 1 shown in Table 4, except that the width of the molten metal surface in the area exposed to the atmosphere was set to 40 mm, 30 kg of molten metal passed through the aforementioned area in 9 seconds in the molten metal flow path provided between the melting furnace and the tundish, the rolling ratio for intermediate rolling (cold rolling) was set to 65%, a second intermediate annealing was performed at 720°C for 20 seconds, and then the rolling ratio for finish cold rolling was set to 14%. The thickness of the sheet after finish cold rolling was 0.60 mm. The copper alloy sheet material according to Example 5 was subjected to the same measurements as in Example 1. The clearance / thickness ratio for press punching was set in the same manner as in Example 1. The measurement results are shown in Table 7 below.
[0064] [Example 6] The chemical composition of the copper alloy was changed as shown in Table 2, the oxygen content in the molten pure copper raw material was set to 49 ppm by mass, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was 75,000 mm². 2Except that 6 kg of molten metal passed through the portion of the molten metal flow path exposed to the atmosphere in 2 seconds in a molten metal flow path provided between the melting furnace and the tundish, a copper alloy sheet material with the composition shown in Table 2 was produced by the same manufacturing method as in Example 4 shown in Table 4. The sheet thickness after finish cold rolling was 2.00 mm. The copper alloy sheet material according to Example 6 was subjected to the same measurements as in Example 1. The clearance / sheet thickness ratio for press punching was set in the same manner as in Example 1. The measurement results are shown in Table 8 below.
[0065] [Example 7] The chemical composition of the copper alloy was changed as shown in Table 2, the oxygen content in the molten pure copper raw material was set to 46 ppm by mass, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was 252,500 mm². 2 Except for the following, a copper alloy sheet material with the composition shown in Table 2 was produced using the same manufacturing method as in Example 5 shown in Table 4, with 27 kg of molten metal passing through the portion of the molten metal flow path exposed to the atmosphere in 8 seconds in a molten metal flow path provided between the melting furnace and the tundish, and the width of the molten metal flow path being 60 mm. The sheet thickness after finish cold rolling was 0.60 mm. The copper alloy sheet material according to Example 7 was subjected to the same measurements as in Example 1. The clearance / thickness ratio for press punching was set in the same manner as in Example 1. The measurement results are shown in Table 8 below.
[0066] [Example 8] Except for changing the chemical composition of the copper alloy as shown in Table 2 and setting the O content in the molten pure copper raw material to 56 ppm by mass, copper alloy sheets with the composition shown in Table 2 were produced using the same manufacturing method as in Example 1 shown in Table 4. The sheet thickness after finish cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material according to Example 8. The measurement results are shown in Table 8 below.
[0067] [Example 9] The chemical composition of the copper alloy was changed as shown in Table 2, the oxygen content in the molten pure copper raw material was set to 74 ppm by mass, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was set to 75,000 mm².2 Except for the fact that 4 kg of molten metal passed through the portion of the molten metal flow path exposed to the atmosphere in 2 seconds in a molten metal flow path provided between the melting furnace and the tundish, copper alloy sheets with the compositions shown in Table 2 were manufactured using the same manufacturing method as in Example 1 shown in Table 4. The thickness of the sheet after finish cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material according to Example 9. The measurement results are shown in Table 8 below.
[0068] [Example 10] The chemical composition of the copper alloy was changed as shown in Table 2, and the surface area of the molten metal exposed to the atmosphere in the molten metal flow path was increased to 392,000 mm². 2 Except for the fact that 46 kg of molten metal passed through the portion of the molten metal flow path exposed to the atmosphere in 13 seconds in a molten metal flow path provided between the melting furnace and the tundish, a copper alloy sheet material with the composition shown in Table 2 was produced by the same manufacturing method as in Example 1 shown in Table 4. The sheet thickness after finish cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material according to Example 10. The measurement results are shown in Table 8 below.
[0069] [Comparative Example 1] Except for changing the chemical composition of the copper alloy as shown in Table 3, using a shaft furnace as the melting equipment, setting the oxygen content in the molten pure copper raw material to 9 ppm by mass, and obtaining an ingot by casting the molten metal in a reducing atmosphere without exposure to air, copper alloy sheets with the composition shown in Table 3 were produced using the same manufacturing method as in Example 1 shown in Table 4. The thickness of the sheet after finish cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material related to Comparative Example 1. The measurement results are shown in Table 9 below.
[0070] [Comparative Example 2] A copper alloy sheet material with the composition shown in Table 3 was produced using the same manufacturing method as Comparative Example 1 shown in Table 6, except that the chemical composition of the copper alloy was changed as shown in Table 3, a shaft furnace was used as the melting equipment, the oxygen content in the molten pure copper raw material was set to 240 ppm by mass, the molten metal was cast in a reducing atmosphere, an ingot was obtained without exposing the flow path to the atmosphere, the rolling rate of the intermediate rolling (cold rolling) was set to 50%, a second intermediate annealing was performed at 720°C for 37 seconds, and then the rolling rate of the finish cold rolling was set to 20%. The sheet thickness after finish cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material related to Comparative Example 2. The measurement results are shown in Table 9 below.
[0071] [Comparative Example 3] A copper alloy sheet material with the composition shown in Table 3 was produced using the same manufacturing method as in Example 1 shown in Table 4, except that the chemical composition of the copper alloy was changed as shown in Table 3, the oxygen content in the molten pure copper raw material was set to 21 ppm by mass, the heating before hot rolling was performed at 895°C for 4.5 hours, the rough rolling rate was set to 82%, the first intermediate annealing was performed at 500°C for 6 hours, the intermediate rolling (cold rolling) rate was set to 64%, the second intermediate annealing was performed at 720°C for 22 seconds, and then the finish cold rolling rate was set to 17%. The sheet thickness after final cold rolling was 0.60 mm. The copper alloy sheet material of Comparative Example 3 was subjected to the same measurements as in Example 1. The clearance / thickness ratio for press punching was set in the same manner as in Example 1. The measurement results are shown in Table 9 below.
[0072] [Comparative Example 4] Assuming an oxygen content of 55 ppm by mass in the molten pure copper raw material, and an area of the molten metal surface exposed to the atmosphere in the molten metal flow path of 10,000 mm² 2 Except for the fact that 1.5 kg of molten metal passed through the portion of the molten metal flow path exposed to the atmosphere in 0.2 seconds in a molten metal flow path provided between the melting furnace and the tundish, a copper alloy sheet material with the composition shown in Table 3 was produced by the same manufacturing method as in Example 1 shown in Table 4. The sheet thickness after final cold rolling was 0.80 mm. The same measurements as in Example 1 were performed on the copper alloy plate material related to Comparative Example 4. The results of each measurement are shown in Table 9 below.
[0073] [Comparative Example 5] Assuming an oxygen content of 64 ppm by mass in the molten pure copper raw material, and an area of the molten metal surface exposed to the atmosphere in the molten metal flow path of 582,000 mm² 2 The ingot was cast by having 60 kg of molten metal pass through the atmospherically exposed portion of the molten metal flow path, which was set up between the melting furnace and the tundish, in 20 seconds. The ingot was then heated at 840°C for 4.5 hours, followed by hot rolling to a rolling ratio of 94%, then rough rolling to a rolling ratio of 83%, and finally the first intermediate annealing at 410°C for 3 hours. After that, an attempt was made to perform intermediate rolling (cold rolling), but many casting defects occurred, and cracks developed during the rolling process, so the production of the copper alloy sheet material was discontinued. The compositional analysis of the sheet material at the time of the interruption of intermediate rolling was performed in the same manner as in Example 1, and the results are shown in Table 3.
[0074] Tables 1 to 9 show the conditions for each process of casting, heating, rolling, and annealing of the copper alloy sheet materials for Examples 1 to 10 and Comparative Examples 1 to 5 described above, as well as the alloy composition, tensile strength, electrical conductivity, compound number density, and press punchability measurements.
[0075] [Table 1]
[0076] [Table 2]
[0077] [Table 3]
[0078] [Table 4]
[0079] [Table 5]
[0080] [Table 6]
[0081] [Table 7]
[0082] [Table 8]
[0083] [Table 9]
[0084] As shown in Tables 1 to 9, the copper alloy sheets of Examples 1 to 10 of the present invention, which were produced by satisfying the predetermined chemical composition, the O content in the molten pure copper raw material during melting and casting, and the conditions of atmospheric exposure, all exhibited good press-punching properties and possessed sufficient electrical conductivity and tensile strength.
[0085] Comparative Example 1 had a lower Ni content than specified in the present invention, a lower O content in the molten pure copper raw material than specified in the present invention, and was melted in a melting furnace under a reducing atmosphere. As a result, the number density of compound particles in the copper alloy sheet material was 0, and the change in shear surface ratio exceeded 3.0, resulting in poor press punching properties.
[0086] In Comparative Example 2, the oxygen content in the molten pure copper raw material was higher than specified in the present invention. Therefore, it is thought that when additive elements were added to the molten metal, oxides and other substances formed from the oxidized additive elements during dissolution separated from the molten metal. Furthermore, because the nickel content in Comparative Example 2 was lower than specified in the present invention, it is thought that even if compounds such as oxides were formed, their particles did not grow to the size specified in the present invention (major axis of 0.03 μm or more). As a result, the change in the shear surface ratio exceeded 3.0, resulting in poor press punching performance.
[0087] Comparative Example 3 had a higher Fe content and a higher total content of Ni, Sn, Fe, P, Zn, and Mg than specified in the present invention, resulting in lower conductivity.
[0088] Comparative Example 4 had a small amount of molten metal exposed to the atmosphere in the molten metal flow path, a short passage time through the area exposed to the atmosphere, a lower number density of compound particles than specified in the present invention, and a change in the shear surface ratio exceeding 3.0, resulting in poor press punching performance.
[0089] In Comparative Example 5, the amount of molten metal exposed to the atmosphere in the molten metal flow path was large, and the passage time through the areas exposed to the atmosphere was also too long, resulting in numerous casting defects. As a result, cracks occurred during the intermediate rolling stage, and it was not possible to obtain a copper alloy sheet of the desired thickness.
Claims
1. Ni in an amount of 0.0005% by mass or more and 0.1% by mass or less, Sn in an amount of 0% to 0.1% by mass, Fe is 0% by mass or more and 0.02% by mass or less, P is 0% by mass or more and 0.02% by mass or less, Zn in an amount of 0% to 0.1% by mass, Mg in an amount of 0% by mass or more and 0.05% by mass or less, O in a concentration of 10 ppm by mass or more and 200 ppm by mass or less, Includes, The remainder consists of Cu and impurities. The total content of Ni, Sn, Fe, P, Zn, and Mg is 0.001% by mass or more and 0.11% by mass or less. On an observation surface parallel to the plate surface, the number density of compound particles with a major axis of 0.03 μm to 4.00 μm is 10,000 particles / mm². 2 That concludes the description of the copper alloy sheet material.
2. The copper alloy plate material according to claim 1, wherein the conductivity is 95% IACS or more and 102% IACS or less.
3. The copper alloy plate material according to claim 1, wherein the average major diameter of the compound particles is 0.035 to 3.00 μm.
4. When the aforementioned copper alloy sheet material is press-punched in a direction parallel to the rolling direction, with clearance / thickness ratios of 0.08 and 0.19, The change in the shear surface ratio (shear surface length / fracture surface length) of the end face (cut surface) is 3.0 or less. The copper alloy plate material according to claim 1.
5. The copper alloy plate material according to claim 1, comprising 0% by mass or more and 0.05% by mass of the aforementioned Zn.
6. A heat dissipation component using a copper alloy plate material according to any one of claims 1 to 5.
7. An electrical component using a copper alloy plate material according to any one of claims 1 to 5.
8. An electronic component comprising a copper alloy plate material according to any one of claims 1 to 5, bonded to an insulating substrate.
Citation Information
Patent Citations
Copper alloy sheet having excellent heat dissipation and repeated bendability
JP2014080679A
Copper alloy sheet material and method for producing copper alloy sheet material
JP2023005017A